The effect of Capsicum pubescens "rocoto pepper" on the in vitro survival of Staphylococcus aureus - Pérez-Cubas, Gildert (2025)
The objective of this research was to evaluate the antimicrobial effect of Capsicum pubescens (rocoto) on the survival of Staphylococcus aureus; a pathogenic bacterium associated with various infections. The study aimed to explore natural alternatives to combat the proliferation of this pathogen, leveraging the antimicrobial properties of rocoto. Extracts of Capsicum pubescens were prepared and their effect on S. aureus isolated from a volunteer donor was evaluated. The incubation method at 4°C and colony counting on blood agar were used, with concentrations of 20%, 25%, and 30% rocoto cream. The results showed that all evaluated concentrations inhibited bacterial growth, with higher effectiveness at 25% and 30% concentrations. The findings suggest that Capsicum pubescens could be an effective natural alternative for the treatment of bacterial infections, particularly those caused by S. aureus, and open the possibility for further investigation into its use in therapies as an alternative to conventional antibiotics.